1993
DOI: 10.1126/science.7684161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction Across the Cell Surface and Through the Cytoskeleton

Abstract: Mechanical stresses were applied directly to cell surface receptors with a magnetic twisting device. The extracellular matrix receptor, integrin beta 1, induced focal adhesion formation and supported a force-dependent stiffening response, whereas nonadhesion receptors did not. The cytoskeletal stiffness (ratio of stress to strain) increased in direct proportion to the applied stress and required intact microtubules and intermediate filaments as well as microfilaments. Tensegrity models that incorporate mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
1,619
3
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,699 publications
(1,686 citation statements)
references
References 48 publications
60
1,619
3
4
Order By: Relevance
“…25,141 Classifications SPIO sizes range greatly from 2 to 3 nm for citrate inhibited growth SPIO, 89 tens of nanometers for polymercoated polycrystalline iron oxide nanoparticles through to micrometers for orally ingestible contrast agents. Larger diameters are available and are useful in such enterprises as cell tracking 134,58 and separation, 73 cell rheology and membrane deformation, 38,151 and as contrast agents for the gastrointestinal tract, 54 but have limited functionality in molecular imaging applications due to their limited accessibility to the neo-and microvasculature. Categories of SPIO, based on their overall diameter (including iron oxide core and hydrated coating), are noted in the literature 152 as oral-SPIO at between 300 nm and 3.5 µm; standard SPIO (SS-PIO) at approximately 60-150 nm; ultrasmall SPIO (US-PIO) of approximately 10-40 nm 156 ; and monocrystalline iron oxide nanoparticles (MION-a subset of USPIO 34 ) of approximately 10-30 nm.…”
Section: Iron Oxide Core Structurementioning
confidence: 99%
“…25,141 Classifications SPIO sizes range greatly from 2 to 3 nm for citrate inhibited growth SPIO, 89 tens of nanometers for polymercoated polycrystalline iron oxide nanoparticles through to micrometers for orally ingestible contrast agents. Larger diameters are available and are useful in such enterprises as cell tracking 134,58 and separation, 73 cell rheology and membrane deformation, 38,151 and as contrast agents for the gastrointestinal tract, 54 but have limited functionality in molecular imaging applications due to their limited accessibility to the neo-and microvasculature. Categories of SPIO, based on their overall diameter (including iron oxide core and hydrated coating), are noted in the literature 152 as oral-SPIO at between 300 nm and 3.5 µm; standard SPIO (SS-PIO) at approximately 60-150 nm; ultrasmall SPIO (US-PIO) of approximately 10-40 nm 156 ; and monocrystalline iron oxide nanoparticles (MION-a subset of USPIO 34 ) of approximately 10-30 nm.…”
Section: Iron Oxide Core Structurementioning
confidence: 99%
“…15 Cells can sense the mechanical properties of their environment and as a response to perceived mechanical stimuli, they generate biochemical activity along with the signal transduction mechanism called mechanotransduction. 16,17 The matrix stiffness can regulate cellular functions including adhesion, 18 spreading, 19 migration, 20 proliferation, 21 and differentiation. 13,22 One of the most commonly used synthetic polymers to investigate the effects of mechanical stimuli on cellular behavior is poly(ethylene glycol) (PEG), which provides precise control of material stiffness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[50] One decade later, Ingber and colleagues showed that cells can sense physical signals of the microenvironment using integrins, and then transmit this information throughout the cytoskeleton up to the nuclear structure, and thereby influence cell response. [51,52] He proposed a tensegrity-based transduction system and opened a new field of research, mechanotransduction. [53,54] Since then multiple features of the physics of the ECM been investigated.…”
Section: Physics Of the Microenvironment And Mechanotransductionmentioning
confidence: 99%